2013
DOI: 10.1007/s00406-013-0405-4
|View full text |Cite
|
Sign up to set email alerts
|

Heart-type fatty acid binding protein and vascular endothelial growth factor: cerebrospinal fluid biomarker candidates for Alzheimer’s disease

Abstract: The main objective of the study was to validate the findings of previous cerebrospinal fluid (CSF) proteomic studies for the differentiation between Alzheimer's disease (AD) dementia and physiological ageing. The most consistently significant proteins in the separation between AD dementia versus normal controls using CSF proteomics were identified in the literature. The classification performance of the four pre-selected proteins was explored in 92 controls, 149 patients with mild cognitive impairment (MCI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 47 publications
1
51
1
Order By: Relevance
“…The study by Guo et al supports the potential of hFABP and VEGF in CSF as AD biomarkers in combination with Aβ42, t-tau, and p-tau181 [89] . precursor, Aβ, apolipoprotein E precursor, serum albumin precursor, keratin type I cytoskeletal 9, and tetranectin) was able to discriminate AD patients from controls with a median accuracy of 95% (sensitivity 85% and specificity 97%) [90] .…”
Section: Pigment Epithelium-derived Factor (Pedf) Haptoglobinmentioning
confidence: 82%
“…The study by Guo et al supports the potential of hFABP and VEGF in CSF as AD biomarkers in combination with Aβ42, t-tau, and p-tau181 [89] . precursor, Aβ, apolipoprotein E precursor, serum albumin precursor, keratin type I cytoskeletal 9, and tetranectin) was able to discriminate AD patients from controls with a median accuracy of 95% (sensitivity 85% and specificity 97%) [90] .…”
Section: Pigment Epithelium-derived Factor (Pedf) Haptoglobinmentioning
confidence: 82%
“…Recently, factors such as heart-type fatty acid binding protein (hFABP) and vascular endothelial growth factor can be a one of important biomarkers in hallmark of AD and other dementias [27]. Amyloid β and phosphorylated tau have been studied to elucidate the mechanism of action of neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due, in part, to the fact that there is mixed epidemiological evidence of risk and resilience when measuring VEGF. High levels of serum VEGF have been associated with an increased risk of stroke (Pikula et al, 2013) and more frequent cerebral microbleeds among individuals with Alzheimer's disease (Zhang et al, 2016), while CSF VEGF levels have been reported to be higher (Tarkowski et al, 2002), lower (Guo, Alexopoulos, & Perneczky, 2013), and equivalent (Blasko et al, 2006) among individuals with AD compared to controls. Perhaps VEGF-related genes like PROK1 will provide clues to help unravel the complex associations among VEGF, cerebrovascular disease, and AD.…”
Section: Discussionmentioning
confidence: 99%